Analysis of clinical trials on biomaterial and therapeutic applications of chitosan: A review. (15th February 2022) - Kantak, Maithili N.; Bharate, Sonali S.
Abstract: Chitosan is a modified natural carbohydrate polymer derived from chitin that occurs in many natural sources. It has a diverse range of applications in medical and pharmaceutical sciences. Its primary and permitted use is biomaterial in medical devices. Chitosan and its derivatives also find utility in pharmaceuticals as an excipient, drug carrier, or therapeutic agent. The USFDA has approved chitosan usage as a biomaterial but not for pharmaceutical use, primarily because of the concerns over its source, purity, and immunogenicity. A large number of clinical studies are underway on chitosan-based materials/ products because of their diverse applications. Herein, we analyze clinical studies to understand their clinical usage portfolio. Our analysis shows that >100 clinical studies are underway to investigate the safety/efficacy of chitosan or its biomaterials/ nanoparticles, comprising 95% interventional and 5% observational studies. The regulatory considerations that limit the use of chitosan in pharmaceuticals are also deliberated. Teaser: Clinical Trials of Chitosan. Graphical abstract: Unlabelled Image